Increased visceral adiposity with normal weight is associated with the prevalence of non‐alcoholic fatty liver disease in Japanese patients with type 2 diabetes. Issue 4 (19th December 2015) - Bouchi, Ryotaro; Takeuchi, Takato; Akihisa, Momoko; Ohara, Norihiko; Nakano, Yujiro; Nishitani, Rie; Murakami, Masanori; Fukuda, Tatsuya; Fujita, Masamichi; Minami, Isao; Mihara, Masatomo; Yoshimoto, Takanobu; et al.
Abstract: Aims/Introduction: To investigate the impact of increased visceral adiposity with normal weight (OB[−]VA[+]) on the prevalence of non‐alcoholic fatty liver disease in patients with type 2 diabetes. Materials and Methods: This was a cross‐sectional study of 140 Japanese patients with type 2 diabetes (mean age 65 ± 11 year; 44.6% women). Visceral fat area (VFA; cm 2 ) and liver attenuation index (LAI) were assessed by abdominal computed tomography. The patients were divided into four groups by VFA and body mass index (BMI; kg/m 2 ) as follows: BMI <25 kg/m 2 and VFA <100 cm 2 (OB[−]VA[−]), BMI ≥25 kg/m 2 and VFA <100 cm 2 (OB[+]VA[−]), BMI <25 kg/m 2 and VFA ≥100 cm 2 (OB[−]VA[+]), and BMI ≥25 kg/m 2 and VFA ≥100 cm 2 (OB[+]VA[+]). Multivariate linear regression and logistic regression analysis were carried out to determine the impact of OB(−)VA(+) on LAI. Results: In the present study, 25.0% were OB(−)VA(+) patients, where the LAI levels were lower (1.09 ± 0.22) than those in OB(−)VA(−) patients (1.23 ± 0.15), and were equivalent to those in OB(+)VA(+) patients (1.03 ± 0.26). In multivariate linear regression analysis, OB(−)VA(+) was independently associated with LAI (standardized β−0.212, P = 0.014). In multivariate logistic regression analysis, OB(−)VA(+) was a significant predictor of LAI <0.9 (odds ratio 5.88, 95% confidence interval 1.03−33.52, P = 0.046). Conclusions: The present study provides evidence that increased visceral adiposity with normal weight is a strong predictor for the prevalence of non‐alcoholic fatty liver disease in Japanese patients with type 2 diabetes. Abstract : This study is first to demonstrate that increased visceral adiposity with normal weight (OB(‐)VA(+)) is associated with non‐alcoholic fatty liver disease (NAFLD) among patients with type 2 diabetes. Despite the accumulation of cardiovascular risks such as high blood pressure, and high LDL, the (OB(‐)VA(+)) patients are less frequently to receive antihypertensive or lipid lowering agents than obese patients with increased visceral adiposity. Visceral adiposity should be directly evaluated for the management of NAFLD and cardio‐metabolic risks among non‐obese patients with type 2 diabetes as well as obese patients.